Concern and action. Cardinal Stefan Wyszyński and West Pomerania - Stanuch, Zbigniew (Studia Theologica Varsaviensia, 2019)
While analysing the attitude of Primate of Poland Cardinal Stefan Wyszyński to West Pomerania, we may enumerate three basic aspects. Firstly, the role which Cardinal played by fulfilling the post of the ordinary of the ordinariate of Gorzów. He was then interested, among others, in the provision of the continuity of management in this territory. Secondly, mainly thanks to his efforts and involvement of bishops of Gorzów, they succeeded in 1972 in dividing the big apostolic administration of Gorzów into three smaller dioceses. Thirdly, the issue concerning the relation with the Christians from West Pomerania is equally significant. Primate was very frequently visiting this region. In the opinion of the author of the article, the words “Concern and action” reflect best his interest in the fate of the Christians, who appeared after the war in the so-called Regained Lands.